THE INFLUENCE OF JOB ROTATION ON IMPROVING QUALITY OF SERVICE AN EMPIRICAL STUDY AT AL-SADR TEACHING HOSPITAL IN NAJAF AL-ASHRAF - Kadhim Thaer Younus (ZILLZELL MEDIA PRIMA, 2024)
The aim of the current study is to determine level of influence job rotation on service quality. The study was applied at Al-Sadr Teaching Hospital on a sample of (85) individuals, based on a questionnaire form, from which (80) questionnaires were retrieved, and (78) questionnaires were valid for testing after excluding (2) unsuitable questionnaires for testing. Due to the nature of the work of the researched organization, the study problem was embodied in the extent to which it is possible to apply the concept of job rotation in its four dimensions (training, job descriptions, functional development, systems and procedures) and the level of reflection of its results on the quality of service provided to patients. Based on the results of the study, The researcher reached several conclusions, the most important of which are: that there is a significant effect of job rotation on the quality of service at a rate of (94.4%) percent. Finally, the study presented a number of recommendations to improve the quality of service in the hospital, the first of which is employing the concept of job rotation and spreading its culture by adopting it as a fixed policy in the hospital to improve the level of service for all patients.